ECONOMIC CRISIS AND THE LEGAL SYSTEM: A TRIAD OF TENSIONS - Kūris, Egidijus (Teisė, 2015)
The article deals with the impact of the world economic crisis that caught Lithuania in 2008, and the measures to overcome it, on Lithuania’s legal system. The legal system is treated as a concept much wider than the system of positive law, statutory and jurisprudential. It includes inter alia legal mentality, legal culture and practice of law-making and law-applying institutions. In this sense, the crisis and the measures designed to overcome it have produced a much wider impact on the legal system, than merely intervention to the positive law (different areas of legal regulation), because the legal standards of a democratic regime have underwent change: the settled standards of the rule of law and the protection of human rights have been lowered as the legal system appeared to be no longer able to secure defence of certain rights. This is a general hypothesis which has to be tested in the framework of the research project “Challenges of the Economic Crisis (Recession) for the Rule of Law and Human Rights”, conducted by the scholars of the Faculty of Law of Vilnius University. This article is introductory in relation to other articles written within the said project and published in this issue of “Teisė”. The articles discusses at length the methodological avenue along which distinct parts of the research have to be further developed, that is dimensions, or fields of tension, where opposition between law and other phenomena show: (i) law v. economic reality; (ii) law v. politics; (iii) law v. society. The research aims at showing how, in each of the segments of the human rights catalogue, and to what extent economic inevitability has induced the lowering of the settled standards of the rule of law and the protection of human rights and, on the other hand, where there lies a boundary of these standards which even economic inevitability is not able to force the legal system to overstep. Also, the research has to show what political initiatives aimed at self-protection of anti-crisis policy (and policy/politics at large) against judicial control have been promoted, and what is the condition of society which either allows these initiatives to be implemented or hinders them. In order to draw on the latter aspect, a representative opinion research was conducted in the framework of the research project, which has produced results testifying of some auspiciousness of the social medium for such situation where policy/politics is less controlled by law than in the pre-crisis times.